Weathered Hydrocarbon Wastes: A Risk Management Primer - Brassington, Kirsty J.; Hough, Rupert L.; Paton, Graeme I.; Semple, Kirk T.; Risdon, Graeme C.; Crossley, Jane; Hay, I.; Askari, K.; Pollard, Simon J. T. (Taylor & Francis, 2007)
We provide a primer and critical review of the characterization, risk assessment, and bioremediation of weathered hydrocarbons. Historically the remediation of soil contaminated with petroleum hydrocarbons has been expressed in terms of reductions in total petroleum hydrocarbon (TPH) load rather than reductions in risk. There are several techniques by which petroleum hydrocarbons in soils can be characterized. Method development is often driven by the objectives of published risk assessment frameworks. Some frameworks stipulate analysis of a wide range of petroleum hydrocarbons; for example, the United Kingdom (UK) approach suggests compounds from EC5 to EC70 be examined. Methods for the extraction of petroleum hydrocarbons from soil samples have been reviewed extensively in the open literature. Although various extraction and analytical methods are available for petroleum hydrocarbons, their results suffer from inter-method variation, with gas chromatography methods being used widely. Currently, the implications for risk assessment are uncertain. Bioremediation works well for remediating soils contaminated with petroleum hydrocarbons. As a result, the optimization of environmental conditions is imperative. For petroleum hydrocarbons in soil, international regulatory guidance on the management of risks from contaminated sites is now emerging. There is also growing support for the move toward compound-specific risk-based approaches for the assessment of hydrocarbon-contaminated land.
Keywords: Environmental; Hydrocarbons; Remediation; Risk management; Weathered